STUDI KOMPARATIF KECENDERUNGAN IMPULSIVE BUYING ANTARA MASYARAKAT PERKOTAAN DENGAN MASYARAKAT PERDESAAN PADA MASA PANDEMI. - Rusmiati, Rusmiati; Buwono, Sri; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aims to find out the differences in impulsive buying tendencies between urban communities and rural communities during the pandemic. The method used is a comparative descriptive research method using inferential statistical analysis techniques. The source of this research data is the urban community, which is located in Kuala Dua and the rural community, which is located in the seburing village. Data collection in this study was obtained from the results of a questionnaire distributed by researchers to respondents. The hypothesis testing used in this study is to use a t test which shows that the hypothesis test results use an independent sample t-test, that the calculated value ttabel and the sig value. (2-tailed) 0.041 0.05, which means Ha is accepted and Ho is rejected, so it can be concluded that there is a significant difference in the tendency to impulsive buying between urban communities and rural communities during the pandemic. As for the differences based on income earned by consumers, basically this study took a sample of respondents who were 23 years old and above and who already had their own income.)